Розробка електродів для кріоконсервування стовбурових клітин за допомогою електропорації з навантаженням сахарозою - Schwäblein, Anna; Khayyat, Diaa; Leal Marin, Sara; Glasmacher, Birgit (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):295